A Aritmética Escolar E O Método Intuitivo: Um Novo Saber Para O Curso Primário (1870 - 1920) - Oliveira, Marcus Aldenisson De [UNIFESP] (2017)
This text is the result of an investigation into the history of mathematics education. The configuration of primary school arithmetic under the aegis of the intuitive wave was admitted as the subject. Governed by the advances in the fields of psychology and physiology, modern intuitive pedagogy was seen as the hallmark of a modernizing project for Brazilian primary education during the period from 1870 to 1920. The historical approach to the epistemological and didactic aspects of Arithmetic based on school textbooks allowed us to characterize the constitution of a new knowledge. Supported by the educational documentation of the period, the investigation analyzed the dynamics of reorganization of the arithmetic knowledge in elementary education. In line with the guidelines of modern pedagogy, such knowledge has been transformed based on the purpose of the school. When primary school had the purpose of imparting individuals with the “petty formula” of knowing how to read, write, and count, for their insertion into the craft of mechanics, commerce, industry, and rural activities, elementary knowledge was identified with rudimentary knowledge: one which is useful and essential for practical life. Nevertheless, when primary school had the purpose of giving all individuals the greatest possible mass of knowledge to guide them into the world of letters, elementary knowledge represented the first foundations of science. Another important aspect that contributed to the configuration of the epistemological status of the elementary knowledge of Arithmetic was the conception of the child/student. When considering the child as a rational being, arithmetical knowledge was structured in the internal logic of matter, respecting the order of student intelligibility. In contrast, when seeing the child as an empirical being, arithmetical knowledge was conceived according to the student’s rhythm of psychological development. As the utilitarian and intuitive approach to teaching became the pedagogical creed of the late nineteenth and early twentieth centuries, primary school was required to work with the essential to the detriment of the fundamental and with the sensitive before the abstract. In this case, the psychologization of the elements of Arithmetic has otherwise characterized the epistemological status of knowledge in relation to the logical-rational elements of encyclopedic inheritance. Based on a typically propaedeutic and abstract rubric to a utilitarian and intuitive matter, the constitution of the intuitive Arithmetic in primary school confirmed the thesis that a pedagogical wave has a key role in the constitution of a new scholastic knowledge.